1996
DOI: 10.1159/000169013
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-Acetyl-Beta-<i>D</i>-Glucosaminidase Activity in Children with Insulin-Dependent Diabetes mellitus

Abstract: Urinary N-acetyl-β -D-glucosaminidase (NAG) is a sensitive indicator of renal tubular injury. The aim of the study is to determine the status of urinary NAG excretion in Chinese children with insulin-dependent diabetes mellitus (IDDM) but without any clinical evidence of nephropathy, and to try to find the possible associated factors of such tubular injury if any. Thirty-one children (8 males and 23 females) with IDDM who have normal serum creatinine, 24-hour urinary creatinine clearance and urinary total prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…[27] Urinary NAGA was found to be increased in children with insulin-dependent diabetes mellitus (IDDM) without any clinical evidence of nephropathy. [28] Such increased excretion correlated with the plasma HbAlc level. There is a tubular dysfunction in the early stage of IDDM children even before there is any clinical evidence of nephropathy, and urinary NAGA may reflect glycemic control in such patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[27] Urinary NAGA was found to be increased in children with insulin-dependent diabetes mellitus (IDDM) without any clinical evidence of nephropathy. [28] Such increased excretion correlated with the plasma HbAlc level. There is a tubular dysfunction in the early stage of IDDM children even before there is any clinical evidence of nephropathy, and urinary NAGA may reflect glycemic control in such patients.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to healthy controls, urinary APN and NAGA were found significantly elevated in glomerulonephritis patients. [28] APN indicates very early tubular impairment and, in some cases, APN is elevated although NAGA is still within normal ranges. [13] In conclusion, damage of tubules in primary glomerulonephritis, lupus nephritis, and diabetic nephropathy is accompanied by a release of several tubular enzymes, with possible diagnostic and prognostic significance.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that urinary excretion of N-acetylglucosaminidase as a sensitive marker of renal tubular damage was increased in patients in the early stages of type-1 [18, 19]and type-2 [20, 21]diabetes. These lines of evidence suggest that hyperglycemia may provide effects on renal tubular cells even in the early stages of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that N-acetyl--glucosaminidase (NAG) activity in urine increased during the development of the early stages of diabetic nephropathy, and is correlated with the increase of urinary microalbumin and other parameters relevant to diabetes (UK Prospective Diabetes Study 1993, Hsiao et al 1996, Kato et al 1997, Yamanouchi et al 1998, Ishii et al 2001. Although NAG is widely distributed in various organs, it is especially concentrated in the epithelial cells of the renal proximal tubules (Price 1992).…”
Section: Introductionmentioning
confidence: 99%